P08.35 Cluster analysis of chlamydia trachomatis strains using two multilocus sequence typing schemes shows differences in discrimination of msm strains versus those of heterosexuals. (13th September 2015) - Versteeg, Bart; Bruisten, Sylvia M; van der Ende, Arie; Pannekoek, Yvonne
Abstract :  Introduction: Despite intensive efforts Chlamydia trachomatis (Ct) remains the most common bacterial sexually transmitted infection worldwide. Therefore, to gain more insight into the epidemiology and transmission of Ct, multilocus sequence typing (MLST) schemes have been developed. However, there is no consensus regarding the use of an MLST scheme for epidemiological studies. Therefore, the objective of this study was to investigate the clustering of Ct strains using two MLST schemes with differing discriminatory capacities. Methods: We selected and tested samples from Ct infected men having sex with man (MSM) and heterosexual women using two existing MLST schemes. One MLST scheme was based on 6 highly variable targets in the chlamydial genome, also referred to as high-resolution MLST (hr-MLST-6) and the other scheme was based on 7 housekeeping genes (MLST-7). For this study, the existing MLST-7 scheme was modified to a nested PCR enabling to test clinical samples. Sequences obtained from both MLST schemes were analysed for cluster analysis and phylogenetic relationships. Results: Full profiles were obtained for 175 samples; 84 (48%) were from MSM and 91 (52%) from heterosexuals. We detected 32 sequence types (STs) using the MLST-7scheme and 78 STs using the hr-MLST-6scheme. Cluster analysis using hr-MLST-6data showed segregation between isolates from MSM and heterosexuals. However, cluster analysis using the MLST-7 data did not show this segregation between isolates from MSM and heterosexuals. Conclusion: The MLST-7 scheme was not able to discern closely related Ct strains over a small time-frame confirming that it is more suitable for evolutionary studies. For short-term cluster analysis the hr-MLST-6scheme is considered more suitable to study the epidemiology and transmission of Ct in various populations. Disclosure of interest statement: This work was funded by the Public Health Service of Amsterdam, the Netherlands. None of the authors report a conflict of interest.